Sex-biased phenotypic plasticity affects sexual dimorphism patterns under changing environmental conditions - Giulia Cordeschi; Daniele Canestrelli; Daniele Porretta (Scientific Reports, 2024)
Abstract Sexual dimorphism is almost ubiquitous in animals. A common pattern observed across multiple taxa involves differences in development time (sexual bimaturism) and body size (sexual size dimorphism) between conspecific males and females. Furthermore, a strict association of dimorphism at these traits has been documented in several taxa, where the sex showing shorter development time also has a smaller body size than the other sex. Growth and development are strongly dependent on environmental conditions during individual life-cycle in ectotherms, inducing considerable phenotypic plasticity. However, how phenotypic plasticity affects the association between sexual dimorphism in development time and body size remains unclear. Here, we tracked development time, body size, and body mass throughout the ontogeny of the mosquito Aedes mariae. The larval development of this species is strictly linked to Mediterranean Sea rock-pools, whose highly variable environmental conditions over minimal time frames make this organism-environment system ideal for exploring plasticity-led eco-evolutionary processes. We found differential plasticity between males and females, dissolving the link between dimorphism in development time and body size under increasing temperature and decreasing salinity conditions. These findings contrast with the current hypotheses proposed to explain the origin of the association between sexual bimaturism and sexual size dimorphism, highlighting the condition dependence of sexual dimorphism patterns and the need to consider phenotypic plasticity in future studies on their evolution.